Implementing Hybrid Filtering on Korean Drama Recommendation Through K Nearest Neighbor Algorithm - Mutiara Ramadhani Sugiri; Viny Christanti Mawardi; Janson Hendryli (Indonesian Journal of Multidisciplinary Science, 2022)
Over time, many cultures from South Korea entered Indonesia, such as music, food, and drama series. From year to year, the number of Korean dramas released increased as well as fans of the Korean drama. Therefore, the researcher aimed to create a system that might help K-drama lovers to sort recommendations regarding favorite dramas. The researcher designed the system, starting from collecting data to calculating adjusted cosine similarity. Based on the results of the user acceptance testing and the answers of the respondents, it can be concluded that the Korean drama recommendation system website's function is effective and provide suggestions based on user ratings.